A REVIEW ON PENTA HELIX ACTORS IN VILLAGE TOURISM DEVELOPMENT AND MANAGEMENT - Putra, Trisna (Journal of Business on Hospitality and Tourism, 2019)
The popularity of village tourism, as a possibility to spend the vacation has increased in Indonesia. There are about 83.344 villages spread all around Indonesia and each of them has their own characteristic with social and culture prosperous. However there is still limited number of village being managed as a product and applied village tourism program successfully. Furthermore, the program does not seem on the right track, not focus and is poorly understood and very weak on implementation. Since the scarce availability of human resources in the village, thus the involvement of different actors and stakeholders become critical and their role as well as participations is matter. The Penta Helix of Government-Community-Business-Academics-Social Entrepreneur is a combination of stakeholder in developing tourism destination. This study applies the content analysis methodology by reviewing seven current journal articles related to village tourism development in Indonesia. This study reviews an extensive literature on village tourism study using the institutional database. Based on the reviews of the articles, this study aims in identifying the stakeholders involved in village tourism development. Furthermore, this study assessed the actor’s specific roles in village tourism development. The result of the study showed that not all tourism stakeholders as proposed by the penta helix model play significant roles in village tourism development. Most of the study on village tourism did not pay attention on the role of academician and social entrepreneur, as the community, government and business were much preferred.